Use of photodynamic therapy in the treatment of oral Candidíases: A literature review (Research, Society and Development, 2023)
Oral candidiasis is a fungal infection, caused by the fungus of the candida genus and the albicans species, it is an opportunistic fungus that usually proliferates When there is an imbalance of the immune system, but there are also Other predisposing factors such as patient's whit uncompensated diabetes, use poorly adapted prostheses, stress, among others. This pathology usually affects the palate, tongue and buccal mucosa. It can present in three forms: pseudomembranous, erythematous and hyperplastic. Treatment is mostly done with provided antifungals. However, photodynamic therapy has been shown to be an effective treatment in cases of oral candidiasis. The methodology of this work was carried out through scientific articles with the aim of analyzing photodynamic therapy in the treatment of oral candidosis and how photodynamic therapy contributes to the treatment of this infection.